Elementary School Students’ Conflict: Fundamental Understanding, Forms, Post-Conflict Effect, and the Involvement of Teachers, Parents, and Friends - Hanum, Citra Bahadur; Agustin, Mubiar; Maftuh, Bunyamin (Universitas Pendidikan Indonesia, 2024)
Elementary school age brings out many differences between students. It does not deny that it can lead to conflict, such as hitting, direct and indirect aggression manifested in the form of verbal abuse, gesture threats, and destruction of property. The impact of mishandling conflict in the school context can cause several negative consequences. This research aims to analyze the student conflict in elementary schools. It used a qualitative approach with a phenomenology method. The research subjects were 55 elementary school students (29 girls and 26 boys) in one city in West Java province. Obtaining further data through the help of research instruments, namely open-ended surveys and in-depth interviews. This research used the Miles and Huberman analysis technique. The result showed that (1) students' comprehension of conflict meaning lies to crime, dispute, problem or riot, argument, and enmity; (2) students found conflict words from the platform and other places they are used to; (3) students’ conflict forms are psychic and verbal; (4) there are the 11 post-conflict effects; (5) other parties’ involvement are students’ friend, teacher, and parents. Students’ fundamental method to understand a conflict is their experience and view relating to the level of conflict concept and handling method. External parties’ involvement is significant in offering help to l students’ conflict impact. The research result is expected as considered for the regulation or juridical matters directed at the knowledge of conflict and ways of handling it.